NEW APPLICATOIN OF LOGISTICS PROCESSING: NEW APPLICATOIN OF LOGISTICS PROCESSING - Bogdanov, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report analyzes the possibility of using analytic hierarchy process in logistics demand forecasting. It proposes a method to estimate parameters of the individual values of the analysis.